Drug delivery and targeting for pharmacists and pharmaceutical scientists - Anya M Hillery (Taylor & Francis, 2001)
An accessible, easy-to-read textbook, this is the first book to provide a comprehensive introduction to the principles of advanced drug delivery and targeting, their current applications and potential future developments.